Long-Term Habitat Fragmentation Is Associated With Reduced MHC IIB Diversity and Increased Infections in Amphibian Hosts - Belasen, Anat M.; Bletz, Molly C.; Leite, Domingos da Silva; Toledo, Luís Felipe; James, Timothy Y. (Frontiers in Ecology and Evolution, 2019)
Habitat fragmentation and wildlife disease are two widespread drivers of biodiversity loss, yet few empirical studies have explored their interactions. In this study, we utilized a naturally fragmented island system to examine the impacts of fragmentation on genetic diversity and amphibian infection dynamics. We determined the impacts of fragmentation on genetic diversity at the immunity locus MHC IIB, a hypothesized predictor of disease susceptibility. Contrary to expectations, island populations lost genetic diversity at this locus while simultaneously experiencing positive selection at MHC IIB. We then used Next-Generation Sequencing to identify a variety of potential eukaryotic parasites from amphibian skin swabs. Island populations exhibited higher potential parasite richness (proportion of eukaryotic microbe operational taxonomic units or OTUs from parasitic taxa) relative to mainland populations. MHC homozygotes hosted a lower diversity of potential parasites, and population-level MHC diversity was negatively associated with parasite richness. Our results show that genetic erosion can occur at the MHC IIB locus following fragmentation, which may contribute to increased susceptibility to parasites.